(untitled) (International Journal of Engineering and Computer Science, 2014)
Privacy Preserving Data Mining has become popular now-a-days to restrict the access of data from unauthorized parties i.e., it guarantees the protection of individual records of particular party. In order to make this possible Privacy Preserving Data Mining provides many techniques like Randomization & cryptography. In our application cryptographic technique has been used to provide security to parties data. Specifically, DES algorithm has been used to encrypt and decrypt the data which has been received from different parties and also, apriori algorithm has been used for analysis of collaborative data of multiple parties. Finally, we proposed an algorithm named privacy preserving Collaborative Data Mining (PPCDM) for successful realization of our framework.